2009
DOI: 10.3347/kjp.2009.47.4.337
|View full text |Cite
|
Sign up to set email alerts
|

Endosymbionts of Acanthamoeba Isolated from Domestic Tap Water in Korea

Abstract: Abstract:In a previous study, we reported our discovery of Acanthamoeba contamination in domestic tap water; in that study, we determined that some Acanthamoeba strains harbor endosymbiotic bacteria, via our molecular characterization by mitochondrial DNA restriction fragment length polymorphism (Mt DNA RFLP). Five (29.4%) among 17 Acanthamoeba isolates contained endosymbionts in their cytoplasm, as demonstrated via orcein staining. In order to estimate their pathogenicity, we conducted a genetic characterizat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 32 publications
1
17
0
Order By: Relevance
“…are ubiquitous free-living amoebae and function as predators, controlling microbial communities. These protists are common in the environment and previously have been detected in some domestic tap water samples [115], mineral BW, and laboratory distilled water [116]. In this study, Acanthamoeba palestinensis was detected in all DW samples except artesian and reprocessed tap BW.…”
Section: Plos Onesupporting
confidence: 57%
“…are ubiquitous free-living amoebae and function as predators, controlling microbial communities. These protists are common in the environment and previously have been detected in some domestic tap water samples [115], mineral BW, and laboratory distilled water [116]. In this study, Acanthamoeba palestinensis was detected in all DW samples except artesian and reprocessed tap BW.…”
Section: Plos Onesupporting
confidence: 57%
“…The strongest positive correlation with L. pneumophila numbers was a Legionella OTU (OTU69) ( ρ = 0.47) . The second highest correlation was with an OTU with a high sequence similarity to Methylophilus ( ρ = 0.37), which is a known endosymbiont of Acanthamoeba [ 45 ].…”
Section: Resultsmentioning
confidence: 99%
“…Besides, it was reported that Methylophilus spp. can live in the cytoplasm of Acanthamoeba isolated from domestic tap water in Korea (Choi et al 2009). The isolated Methylophilus bacteria are strictly aerobic, obligate methylotrophs using methanol as the growth substrate, and can form EPS (Doronina et al 2005;Gogleva et al 2010).…”
Section: Discussionmentioning
confidence: 99%